Personalization of knowledge, personal knowledge ecology, and digital nomadism. (12th February 2019) - Jarrahi, Mohammad Hossein; Philips, Gabriela; Sutherland, Will; Sawyer, Steve; Erickson, Ingrid
Abstract : We examine the concept of personal knowledge management using data drawn from our study of digital nomads. We make two contributions: an empirical and conceptual development of knowledge management as it relates to independent workers and an advancement of social informatics that builds on Gibson's ecological perspective. Digital nomads provide an empirical basis to better understand how knowledge management is shifting from organization‐centric, with its concomitant emphasis on organizational information systems, to worker‐centric, which relies on personal knowledge ecologies. We advance this concept as a combination of personal knowledge management activities and the digital technologies that support them. Our data make clear that individuals are the locus of personal knowledge ecologies, but these ecologies are embedded in a larger community of collaborators, clients, and peers who are often extensively mediated by digital technologies. This embedding and mediation are at the core of the sociotechnical arrangements that define the personal knowledge ecologies that we document.